2022
DOI: 10.3390/plants11040493
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Modus Operandi of Class II KNOX Transcription Factors in Secondary Cell Wall Biosynthesis

Abstract: Lignocellulosic biomass from the secondary cell walls of plants has a veritable potential to provide some of the most appropriate raw materials for producing second-generation biofuels. Therefore, we must first understand how plants synthesize these complex secondary cell walls that consist of cellulose, hemicellulose, and lignin in order to deconstruct them later on into simple sugars to produce bioethanol via fermentation. Knotted-like homeobox (KNOX) genes encode homeodomain-containing transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We were therefore able to infer the potential roles of lncRNAs in cell-specific functions on the basis of their co-expression patterns with PCs when lncRNAs and PCs were regulated by a common set of upstream regulators. In xylem cells, our analysis identified the regulons of ANAC007 ( VND7 ) and ANAC030 ( VND4 ) ( Figure 5 A and 5B)—NAC-domain TFs necessary for xylem formation ( Kubo et al., 2005 )—and xylem-specific regulons of MYB103 , MYB46 , and ANAC073 ( SND2 )—TFs that regulate secondary wall biosynthesis in xylem tissues ( Ohman et al., 2013 ; Zhong et al., 2021 ; Nookaraju et al., 2022 ). The predicted target (protein-coding) genes of these regulons, including WOX14 ( Denis et al, 2017 ) and ANAC075 ( SND4 ) ( Zhong et al., 2021 ), were functionally enriched in biological pathways related to “xylem development” ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…We were therefore able to infer the potential roles of lncRNAs in cell-specific functions on the basis of their co-expression patterns with PCs when lncRNAs and PCs were regulated by a common set of upstream regulators. In xylem cells, our analysis identified the regulons of ANAC007 ( VND7 ) and ANAC030 ( VND4 ) ( Figure 5 A and 5B)—NAC-domain TFs necessary for xylem formation ( Kubo et al., 2005 )—and xylem-specific regulons of MYB103 , MYB46 , and ANAC073 ( SND2 )—TFs that regulate secondary wall biosynthesis in xylem tissues ( Ohman et al., 2013 ; Zhong et al., 2021 ; Nookaraju et al., 2022 ). The predicted target (protein-coding) genes of these regulons, including WOX14 ( Denis et al, 2017 ) and ANAC075 ( SND4 ) ( Zhong et al., 2021 ), were functionally enriched in biological pathways related to “xylem development” ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, KNOX2 also acts as negative regulator of secondary cell wall biosynthesis (Wang et al 2020). ELK Domain acts as a signal for nuclear localization and is included in protein -protein interaction (Nagasaki et al 2001;Ito et al 2002;Nookaraju et al 2022). Homeobox KN Domain acts as transcription factor that is conserved in different plants, which also affects in leaf shape elaboration (Wang & Jiao 2020;Zhang et al 2022).…”
Section: The Analysis Of Amino Acid Sequencementioning
confidence: 99%
“…Based on ColabFold modelling, we investigate the location of domain, which is KNOX1, KNOX2, ELK Domain and Homeobox KN Domain in 3D structural prediction (Figure 7). KNOX1 and KNOX2 domains are formed into MEINOX domain which is separated by a poorly conserved linker sequence (Nookaraju et al 2022). MEINOX Domain that is located in N-terminus will interact with POX domain from BEL protein (Zhang et al 2021).…”
Section: Protein Modelling Of Poh1 Protein and Its Domain Functionmentioning
confidence: 99%
“…After cell wall expansion, SCW deposition occurs. Several excellent reviews have been reported recently on this subject, so please see [ 79 , 80 , 81 , 82 ].…”
Section: Cell Expansion: Determining the Final Shape And Size Of The ...mentioning
confidence: 99%